Spices laid out for drying in the verandah - Mumbai Archive Project Team (Jio Institute, 2024)
Spices are laid out for drying in the verandah of a house in Vasai. Old houses typically had a long verandah or an inner courtyard where this activity was done. In houses that do not have a verandah, the spices are laid out by the side of the road or on rooftops.